2004
DOI: 10.1007/s00059-004-2625-x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Inflammation in Aging

Abstract: Although epidemiologic studies have revealed that high plasma cholesterol or high homocysteine levels, as well as diabetes, hypertension and smoking are important risk factors for atherosclerotic vascular disease, the deleterious effects of these conditions can be delayed or significantly attenuated by therapeutic interventions. Since the population in the Western world is aging, advancing age itself became one of the most significant risk factors for the development of atherosclerosis. Atherosclerosis is a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 80 publications
4
49
0
1
Order By: Relevance
“…Several studies in different tissues have shown that normal aging is associated with a pro-inflammatory, pro-oxidant state that may favor an exaggerated response to injury and degenerative diseases (Choi et al 2010;Csiszar et al 2003;Ungvari et al 2004) and that increased activity of local angiotensin via angiotensin II type 1 receptors is involved in agerelated degenerative diseases (Basso et al 2005;Mukai et al 2002). In agreement, we have recently observed an age-related increased angiotensin activity in the nigra that may increase the vulnerability of Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies in different tissues have shown that normal aging is associated with a pro-inflammatory, pro-oxidant state that may favor an exaggerated response to injury and degenerative diseases (Choi et al 2010;Csiszar et al 2003;Ungvari et al 2004) and that increased activity of local angiotensin via angiotensin II type 1 receptors is involved in agerelated degenerative diseases (Basso et al 2005;Mukai et al 2002). In agreement, we have recently observed an age-related increased angiotensin activity in the nigra that may increase the vulnerability of Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that angiotensin II, acting via type 1 receptors, is one of the most important known inducers of inflammation and oxidative stress in several tissues (Mattson and Maudsley 2009;Min et al 2009;Ruiz-Ortega et al 2001). Normal aging has been associated with a pro-inflammatory, pro-oxidant state that may favor an exaggerated response to injury and degenerative diseases (Choi et al 2010;Csiszar et al 2003;Ungvari et al 2004). In accordance with this, several recent studies have suggested the potential of inhibition of angiotensin for treatment of age-associated diseases and longevity (Benigni et al 2009(Benigni et al , 2010Mattson and Maudsley 2009;Nishiyama et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…35). Vascular aging is characterized by increased oxidative stress (11,13,35), associated with an enhanced rate of endothelial apoptosis (15) and vascular inflammation (51). Thus future studies should elucidate whether antioxidant, antiapoptotic, and anti-inflammatory actions of resveratrol contribute to its antiaging vasculoprotective effects in the elderly (35).…”
Section: Discussionmentioning
confidence: 99%
“…In blood vessels, the cell membrane-associated NAD(P)H oxidase is a significant source of ROS production, and an increased vascular NAD(P)H oxidase has been shown to contribute importantly to the symptoms of vascular aging, including increased O 2 Ϫ ⅐ production, decreased bioavailability of the vasodilator and anti-apoptotic NO (1,12,13,15,19,24,37), increased cardiac oxygen demand (1), and vascular inflammation (Ungvari Z, unpublished observation). EB fluorescence measurements revealed that both the endothelial and smooth muscle cells of NMR vessels produce O 2 Ϫ ⅐ (Fig.…”
Section: Discussionmentioning
confidence: 99%